Analysis of Students' Problems on the Reading Section of TOEFL - Tri Ilma Septiana (IAIN Syekh Nurjati Cirebon, 2021)
In the present study, TOEFL as a standardize test is used UIN Sultan Maulana Hasanuddin as one of requisites to complete study. This study aims to analyze the most difficult reading skills for students of English Education Department (further glossed by EED) and their problems on the reading section of TOEFL. It employed a case study, in which 22 EED students were involved in the TOEFL test which carried out by Language Development Center, UIN Sultan Maulana Hasanuddin Banten. There were three instruments used: archival record of TOEFL test, questionnaire and interviews. The findings of this study found that finding main idea was the most difficult reading skills, Meanwhile, some problems of EED students on the reading section of TOEFL test were limited vocabulary mastery, lack of grammatical knowledge and reading skills, unfamiliar with the topic, as well as low concentration, physical endurance, and limited time.